Kearifan Lokal: Tinjauan Unsur Sosiologi Pembentukan Peraturan Daerah - Benjamin Carel Picauly; Natanel Lainsamputty (Faculty of Law, Universitas Pattimura, 2020)
The protection of local wisdom as a social element in the formation of regional regulations will result in effective and well implemented regional regulations. The purpose of this study is to explain and analyze local wisdom that can play a role in the implementation of good governance in accordance with the conditions of local communities. The research method used normative research with a statutory approach and a conceptual approach and was analyzed descriptively qualitatively. The research results show that there is legal protection of local wisdom through an inventory mechanism and stipulation through local regulations, so that any formation of local regulations can accommodate the values of local wisdom that exist in the community.